The effects of high gravitational stress on the expression of stress response genes in Arabidopsis thaliana - Zappia, Sophia Alessandra (Proceedings of the Wisconsin Space Conference, 2020)
As humans venture farther into space, we are increasingly interested in how plants respond to the unique conditions of spaceflight. This experiment focuses on how gene expression in the model plant Arabidopsis thaliana is affected by high-gravitational stress that is comparable to the amount experienced on a small model rocket. The genes chosen have been studied previously for their roles in mechanical stress and pathogen response. Our results showed an increase in expression of the genes TCH2, TCH3, and MPK3, no change in the expression of CBP60g, and a decrease in the expression of RCI3 and ICS1. These results are largely consistent with spaceflight data and warrant further investigation into the effects of rocket launch on plant growth.